Financial Education in EJA: proposal of a didactic sequence in the light of the Theory Critical Meaningful Learning (Research, Society and Development, 2020)
Financial Education worked in the school context seeks to make students able to be critical when analyzing financial issues that arise in their daily lives and/or in the society in which they live. To this end, it is necessary to discuss a Financial Education curriculum and invest in the preparation of specific didactic materials of a financial nature and their implementation in the classroom. In this context, we present a didactic sequence elaborated for application in the Youth and Adult Education (EJA) modality based on the principles that facilitate critical meaningful learning, described by Moreira with the purpose of developing students' financial thinking and criticality regarding situations on the theme Financial Education (EF). It is a study of qualitative approach, of bibliographic / documentary type, located in the field of Mathematical Education and based on the Theory Critical Meaningful Learning. The proposed activities include the concepts of ratio, proportion, percentage, rule of three, simple and compound interest. Structurally, the sequence articulates six distinct strategies, namely: semi-structured questionnaire, class diary, textbook, questions from the National Examination for Competence Certification for Youth and Adults (Encceja) complemented to everyday situations and the Novak conceptual mapping technique. It was found that the articulation of different materials prepared for EJA combined with the theoretical assumptions of TASC can constitute a teaching strategy to develop financial thinking and criticality and assist students in establishing links between the concepts studied in the formal environment from teaching to practical everyday situations.